Sustaining Interdisciplinary Collaboration : A Guide for the Academy - Bendix, Regina; Noyes, Dorothy; Bizer, Kilian (Book collections on Project MUSE., 2017)
Both a vision for future scholarship and a slogan for university restructuring, interdisciplinarity promises to break through barriers to address today's complex challenges. Yet even high-stakes projects often falter, undone by contradictory incentives, bureaucratic frameworks, communication breakdowns, and the strong feelings raised by urgent social debates. This work examines this topic.